Use of Active Games in Physical and Tactical Training of Young Handball Players at the Initial Stage - Ihor Hrynchenko; Asia Tykhonova; Tеtiana Karpunets; Olexandr Chupryna (Educational Challenges)
The purpose of the study is to increase the effectiveness of physical and technical training of young handball players aged 10-11 by means of moving games, game exercises and relays at the stage of initial training during the pedagogical experiment in 2020-2021.